Modelling and Analysis of Photovoltaic Grid Interfaced System using P&O Algorithm based MPPT - Kundu, B; Mondal, S; Roy, S; Giri, SK; Pal, S (International Journal of Computer Sciences and Engineering, 2025)
Integration of Photovoltaic (PV) systems plays a significant role to reduce the use of fossil fuel consumption in microgrids. In present scenario, fuel reserves are the great challenges which can be met up with plenty of solar irradiance. In this paper, we present modelling of a grid connected PV system. The MATLAB / Simulink is used to establish a model of photovoltaic array. The Simulink model is tested with different temperature and irradiation and resultant I-V and P-V characteristics proved the validation of Simulink model of PV array. Maximum Power Point Tracking (MPPT) Technique using P&O algorithm has been used as control strategy to extract maximum power from PV module. The VSC controlled method along with three level bridge inverter is used to convert the DC voltage to AC. The proper choice of RC bank subsequently reduces the harmonic effects to synchronize the output with the grid voltage. Simulation results are presented to observe the performance and dynamic behaviour of the proposed system.